Statistical analysis of vancomycin-resistant enterococci isolated from the blood of patients in Lithuania - Matylonok, T.; Polishchuck, N. M.; Algirdas, G.; Поліщук, Наталія Миколаївна (My University, 2024)
The widespread dissemination of vancomycin-resistant enterococci (VRE) poses a serious threat to the modern healthcare system. Currently, in most hospitals in Lithuania, VRE is among the most common pathogens causing infections in patients due to medical interventions. A crucial step in combating the spread of VRE is considered to be the continuous monitoring of the circulation of these strains, as well as comprehensive study of their biological properties.
Polishchuck N. M. - ORCID iD 0000-0002-9791-5818
Keywords: vancomycin resistant enterococci (VRE); healthcare-associated infections; blood